Structure based drug design for antifungal agents (aspergillus niger) from synthesis of benzaldehyde derivatives - Abdul Razak., Ahmad Asraf (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Aspergillus niger is a type of fungal and known to be agents of pulmonary aspergillosis for patient with immunodeficiency. Pharmacophore modelling was a new approach to search for potential antifungal agents. From the Protein Data Bank website, Human Aurora A model with PDB ID of 3QBN was chosen as target compound and their 3D structure was generated in LigandScout 3.12 for structure-based pharmacophore. Twelve (12) benzaldehyde derivatives were proposed as test set. The target compound and the test set were fitted to determine the overlapping features between both compound and the pharmacophore fit-values of compounds. The benzaldehyde derivatives were synthesized via Schiff base reaction. The characterization of the synthesized compounds was determined using Nuclear Magnetic Resonance (1H and 13C NMR) and Fourier Transform Infra-Red spectroscopy. Biological evaluation was conducted using brine shrimp lethality test for cytotoxicity. The bioassay test for antifungal was also conducted. The pharmacophore modelling showed that compound (2) 2-hydroxy-N'-[(E)-phenylmethylidene]benzohydrazide has the most interaction to E9Z1A active site which is three interaction to nine amino acid. The biological evaluation by using cytotoxicity showed that compound (2) is less toxic. The antifungal assay indicate that compound (2) inhibit the growth of fungal. Therefore, compound (2) was chosen as suitable lead compound for antifungal agent.